Controlled self-assembly of glycoprotein complex in snail mucus from lubricating liquid to elastic fiber. Issue 25 (12th April 2018) - Zhong, Tianyi; Min, Liu; Wang, Zhiyuan; Zhang, Feng; Zuo, Baoqi
Abstract : Terrestrial snail could intelligently employ elastic fibers clinging itself onto the inverted smooth plate. Abstract : The pedal mucus secreted by many gastropod mollusks, such as terrestrial snails and slugs, plays crucial roles in locomotion, osmoregulation, reproduction, and repulsing predators. In this report, we presented an intriguing example that terrestrial snail can utilize the self-assembly of glycoprotein complex in secreted mucus at the nanoscale to enhance adhesive force on smooth plates. With increasing crawling angle, the structural transformation of pedal mucus was found to involve at least four distinct stages: assembly of nanoparticles, aggregation into microspheres, formation of gels and solidification into fibers. These forming processes were mainly attributed to the unique combination of amino acid composition and chemistry in secreted glycoprotein coupled with the calcium carbonate regulation in pedal gland. Most importantly, we were inspired by these forming process to obtain a novel biomimetic fiber with good extensibility and elasticity from extracted pedal mucus for potential biomedical application.